2020
DOI: 10.1177/1354816620901955
|View full text |Cite
|
Sign up to set email alerts
|

Mountain bike tourism economic impacts: A critical analysis of academic and practitioner studies

Abstract: Mountain biking as a sport and recreational activity has grown rapidly over the previous two decades. Consequently, there has been growth recently in efforts aimed at stimulating mountain bike tourism through the development and marketing of mountain bike trails and parks. Various community advocates, academics, and industry practitioners have sought to quantify the economic impacts of mountain bike tourism to garner public and other financial assistance to aid the development of mountain bike tourism. This re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 25 publications
0
12
0
1
Order By: Relevance
“…From the literature review, many studies were identified that evaluate different categories of sports cycling events in different parts of the world. Many of these studies assess the profile of the mountain bikers' profiles or analyze the economic impact of the events ( Buning et al, 2016 ; Buning & Lamont, 2020 ; Perić et al, 2019 ). The main conclusions suggest that holding mountain bike events is beneficial to the host destination, through positive economic returns and an enhanced image.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…From the literature review, many studies were identified that evaluate different categories of sports cycling events in different parts of the world. Many of these studies assess the profile of the mountain bikers' profiles or analyze the economic impact of the events ( Buning et al, 2016 ; Buning & Lamont, 2020 ; Perić et al, 2019 ). The main conclusions suggest that holding mountain bike events is beneficial to the host destination, through positive economic returns and an enhanced image.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last twenty years, the most commonly studied aspects of mountain bike events have been analyses of participant profiles ( Cessford, 1995 ; Getz & McConnell, 2011; Roberts, Jones, & Brooks, 2018), comparisons of mountain biker profiles with other sports participants (Getz & McConnell, 2011; Kruger, 2014 ), analyses of the economic impacts for host locations ( Buning & Lamont, 2020 ; Moran, Tresidder, & McVittie, 2006 ) and studies of sustainability and environmental impacts ( Freeman & Thomlinson, 2014 ; Goeft & Alder, 2001 ; Symmonds et al, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, the popularity of cycling tourism has grown, not only mountain biking but also e-biking, which has started to become popular [39,[51][52][53]. A recent study from Austria reported that bike tourism will be a significant part of rural economics.…”
Section: Frequency Of the Forest Visits According To The Driversmentioning
confidence: 99%